Spatial Statistic Applied to Incidence Studies of Cancer. - Jane Kelly Oliveira Friestino; Denisa Mendonça; Pedro Oliveira; Carla M. Oliveira; Rosemeire de Olanda Ferraz; Djalma de Carvalho Moreira Filho (Universidade de Brasília, 2016)
The Geographic Information System (GIS) as a tool in epidemiological studies has become something common in the area of Public Health. In studies on cancer incidence, analysis spatial is still in its infancy in the country; however possess great potential to aid in health planning models. The aim of this paper is to present an empirical method of spatial patterns analysis in cases of incidence of rare considered cancers that affect the population aged 0 to 19 years, discussing the applicability of spatial statistics and the possible uses of interpretation of the spatial arrangement of events. We used the GIS to georeference the incidence rates of cases of cancers of some groups of the International Classification of Childhood Cancer (ICCC), adjusted for age and gender, per health centers area from residences. Standardized Morbidity Ratios - SMR were estimated. To control the instability of rates due to the small number of cases, a smoothing the Empirical Bayes method was applied. Comparing the annual rates softened by Empirical Bayes it was found differences between them as the spatial distribution, with concentration of these regions in Southwest and Northwest of the city of Campinas, SP. In conclusion, the use of spatial statistics as a decision support tool can be identify the distribution of cases of ICCC group of cancers, contributing to the health planning.